THE EFFECT OF TRI HITA KARANA-BASED PROBLEM-BASED LEARNINGMODEL ON ECOLOGICAL ATTITUDES AND LEARNING OUTCOMES - Kade Dwi Suarni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the effect of Tri Hita Karana-based problem-based learning model on ecological attitudes and natural science (IPA) learning outcomes. The research type is a quasiexperimental with non-equivalent post-test-only control group design. The research population is 135 students, while the research sample is 61 students. The sampling technique used cluster random sampling techniques. Data collection methods were questionnaires and tests. Data on ecological attitudes werecollected by questionnaire, while data on students' natural science (IPA) learning outcomes were collected by natural science (IPA) learning outcomes test. The data analysis used was Manova. Based on the research that has been conducted, it is concluded that 1) there is a significant effect of the ProblemBased Learning model based on Tri Hita Karana on students' ecological attitude, 2) there is a significant effect of Tri Hita Karana-based Problem-Based Learning model on students' natural science (IPA) learning outcomes, and 3) simultaneously, there is a significant effect of Tri Hita Karana-based ProblemBased Learning model on students' ecological attitudes and natural science (IPA) learning outcomes.